Fatwa DSN-MUI dan SAC Malaysia terhadap Fintech Syariah: : Studi Analisis Akad, Perlindungan Konsumen dan Pengawasan Syariah - Adinda Selvina Adhani; Iskandar Ritonga (At-Taradhi Jurnal Studi Ekonomi, 2026)
The rapid expansion of Islamic fintech across Southeast Asia outpaces the harmonization of Sharia governance, creating cross-border regulatory uncertainty. This study conducts a systematic comparative document analysis of the frameworks issued by Indonesia’s DSN-MUI and Malaysia’s Shariah Advisory Council (SAC) across three instruments: e-money, P2P financing, and equity crowdfunding (ISCF/ECF-i). Using a structured comparative matrix built around contract structure, consumer protection, and Sharia supervision, the analysis evaluates primary legal fatwas and regulatory guidelines from both nations alongside secondary academic literature. The comparison reveals distinct operational trade-offs rather than a single superior model: (1) Indonesia (DSN-MUI): Adopts a contract-specific, instrument-by-instrument approach that maximizes legal certainty but fragments supervision across decentralized Sharia Supervisory Boards (DPS); (2) Malaysia (SAC): Applies principle-based, centrally binding rulings under national financial acts, achieving regulatory consistency at some cost to sectoral specificity. To bridge these gaps, this study proposes a hybrid governance framework that combines Indonesia's contract-certainty approach with Malaysia’s centralized, legally binding supervisory architecture. Ultimately, it outlines concrete regulatory, industry, and research implications for advancing the cross-border harmonization of Islamic fintech governance.